MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPS DENGAN MENGGUNAKN METODE PROBLEM SOLVING DI KELAS IV SD NEGERI 35 AMBACANG KAMBA KECAMATAN BAYANG - NOFRIZA NOFRIZA (Inovasi Pendidikan, 2018)
IPS learning draft form by using the method of problem solving based on measures of problem solving method that consists of six steps. Learning to use a method of problem solving is divided into three phases, namely initial activity, core activities, and weekend activities. Forms implementing problem solving methods are: the implementation of social studies learning by using the methods of problem solving should be in accordance with the learning steps that have been designed. In the early stages of activation activities conducted prior knowledge of the students and asked questions about the picture. At the core stage implemented measures ranging from the problem solving obvious problems to be solved, formulate the problem, formulate hypotheses, data or information that can be used to solve the problem, test the hypothesis up to determine the choice of completion. In the final phase of activities the students are directed to conclude the lesson and give the final test. Learning problem-solving (problem solving) can improve learning outcomes of students, it is seen from the achievement of learning outcomes of students at the end of the action. Where the learning outcomes of students increased from an average of 6.2 in the first cycle to an average of 8.6 in the second cycle. Keywords: Problem Solving Methods, Results Learning, Students, IPS